Union collusion and intra-industry trade - Straume, Odd Rune (2002)
This paper analyses the scope for collusive behaviour within the context of an international duopoly supergame in which both firms and monopoly labour unions interact strategically. We find that the presence of unions, implying an endogenisation of production costs, dramatically alters the incentives for inter-firm collusion. There are, however, strong incentives for the unions to collude, raising the wage above the equilibrium level of the one-shot game. We propose two candidates for a Nash equilibrium of the supergame, in both of which the unions collude. The main result of the paper is that the presence of unions could actually promote intra-industry trade as an equilibrium outcome of the infinitely repeated game.